The Role of Data Analytic to Enhance Design Thinking Process in Producing Social Media Contents - Soeherman, Bonnie; Leonardo Soeherman, Calvin (Information & Media, 2025)
Introduction. This research explains how the integration of roles and optimization of data analytics within the design thinking process can develop social media accounts organically. Method. This study uses an auto-netnography method that focuses on the process of figuring out the output of the data from content analysis and active participant observation on a YouTube channel. Analysis. The triangulation process is carried out by confirming the data from observations as well as the analytics data provided for users and account managers on YouTube. We carry out the interpretation process reflectively, drawing from personal experiences on social media to enrich the meaning. Results. Data analytics enhances the reliability of data on audience behavior due to its ability to optimally process big data and present the data in visual form, thereby increasing the speed and accuracy of decision-making. Data analytics plays a role in all stages of design thinking from empathizing, ideating, creating, to socializing. Conclusions. This research found the effective role of social media platform data analytics in the account development process through the design thinking process. This finding fills a research gap regarding social media data analytics, which has not been widely linked to the content production process.
Keywords: data analytics; design thinking; social media; big data; machine learning